Discussion on the Current Situation and Countermeasures of Regional Community Education: Taking Tongren City, Guizhou Province as an Example - Song, Biaoqian (Journal of Theory and Practice of Contemporary Education, 2023)
The report of the 19th National Congress of the Communist Party of China (CPC) put forward that "we should do a good job in continuing education, speed up the construction of a learning-oriented society, and vigorously improve the quality of the people." The Opinions of the Ministry of Education and other nine ministries and commissions on further promoting the development of community education emphasized that community education is an important part of China's education and an important part of community construction. The Outline of the National Medium and Long-term Education Reform and Development Plan (2010-2020) clearly points out that we should vigorously develop urban and rural community education and build a flexible and open education system for all, lifelong education and modern open education covering both urban and rural areas. It can be seen that community education is an indispensable and important part of the national education system. It is not only the needs of the masses for lifelong learning, but also the needs of the construction of a well-off society in an all-round way. It is also the "people's growing need for a better life". Therefore, it is urgent to explore community education in poverty-stricken areas.Community education is an important part of China's education and an important part of community construction, with regional characteristics. According to the regional characteristics of community education, it is of great theoretical and practical significance to explore an open, shared and sustainable development path of community education and construct a new era community education model to meet the learning needs of different groups.